Enrichment of Artemia metanauplii in phospholipids and essential fatty acids as a diet for common octopus (Octopus vulgaris) paralarvae. (28th August 2013) - Guinot, D.; Monroig, Ó.; Navarro, J.C.; Varó, I.; Amat, F.; Hontoria, F.
Abstract: Highly unsaturated fatty acids (HUFA), like the eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids and polar lipids (essentially phospholipids, PL) have been identified as essential nutrients for common octopus ( Octopus vulgaris ) paralarvae. However, they are not available in sufficient amounts in live preys as Artemia, making necessary a supplementation of these nutrients previous use. A commercial emulsion, soya liposomes, and marine and soya lecithins were used to supply HUFA and PL to Artemia metanauplii, those being regarded as suitable size preys for octopus paralarvae. Our results prove that a simultaneous enrichment in HUFA and PL is possible using enrichment diets combining HUFA‐ and PL‐rich products in short‐term (4 h) incubations. Particularly interesting was the enrichment efficiency shown by the marine lecithin, which enabled the enhancement of the PL fraction of Artemia metanauplii and, importantly, also their HUFA with a remarkable 13% DHA of total fatty acids. Marine lecithin arises as a novel enrichment diet for Artemia and more effective than some commercial products currently used in hatcheries worldwide.